Assessing the relationship between knowledge and the actual use of contraceptives among childbearing women in South-South Nigeria: evidence from the 2018 Nigeria demographic and health survey - Vitalis U. Ukoji; Princewill O. Anele; Chukwuechefulam K. Imo (BMC, 2022)
Abstract Background Nigeria has one of the world's highest fertility rates, which is detrimental to its public health and socioeconomic growth. Despite several efforts by the country and other development partners to reduce high fertility by increasing contraceptive use, the contraceptive prevalence rate among childbearing women remains low, particularly in the South-South compared to other Southern regions. This study, therefore, assessed the relationship between knowledge of and actual use of contraception among women in South-South Nigeria. Methods The study employed a cross-sectional analysis of a nationally representative weighted sub-sample of 4,553 South-South childbearing women extracted from the 2018 National Demographic and Health Survey dataset. The dataset was weighted and examined for missing values that were excluded during the analyses at univariate, bivariate, and multivariate levels. The analyses involved a baseline descriptive analysis, a chi-square test, and logistic regression models using Stata software. The results of the explanatory variables were presented as odds ratios (OR) and 95% confidence intervals (CI). Results Eighty-two per cent of the respondents knew at least one form of contraception, while approximately 82% never used any contraceptive method. The likelihood of using any contraceptive method increased among those who knew about contraceptives (aOR: 1.40; CI: 0.93-2.11). Also, contraceptive use was significantly higher among women and their partners who had post-primary education (aOR: 1.34; CI: 1.25-2.43 and aOR: 1.74; CI: 1.25-2.43, respectively). Furthermore, the prevalence of contraceptive use among women significantly increased with an increase in the household wealth index. Similar results were recorded among women who had five or more living children, who were residents of Rivers State, were married or lived with their partners, were aged 35 years or older, and were currently working. Conclusions Contraceptive knowledge was high but did not translate into actual practice among childbearing women in South-South Nigeria. The use of any contraception was highly influenced by contraceptive knowledge, education, age, marital status, place of residence, and household wealth index, among others. Therefore, some policy issues relating to contraceptive knowledge and actual adoption must be addressed to improve the low rate of contraceptive use in Nigeria.